2010
DOI: 10.1007/s00441-010-1016-2
|View full text |Cite
|
Sign up to set email alerts
|

Aging of cerebellar Purkinje cells

Abstract: Cerebellar Purkinje cells (PCs), the sole output neurons in the cerebellar cortex, play an important role in the cerebellar circuit. PCs appear to be rather sensitive to aging, exhibiting significant changes in both morphology and function during senescence. This article reviews such changes during the normal aging process, including a decrease in the quantity of cells, atrophy in the soma, retraction in the dendritic arborizations, degeneration in the subcellular organelles, a decline in synapse density, diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 92 publications
(125 reference statements)
1
43
0
Order By: Relevance
“…The concomitant reduction of dendritic spines on the hippocampal neurons would be the underlying cause. It would appear therefore that dendritic change is a common feature affecting most central neurons such as pyramidal neurons in the medial prefrontal cortex (Grill and Riddle, 2002), motor cortices (Nakamura et al, 1985) and hippocampus (Luine et al, 2011), cerebellar Purkinje neurons (Zhang et al, 2010) and retinal ganglion cells (Samuel et al, 2011). It is suggested that regression in dendritic arbor and loss of dendritic spines on layer III, layer V primary somatosensory cortical neurons or hippocampal CA1 pyramidal neurons as observed in this study in aging rats may reflect different degrees of degenerative changes that might be induced by regional changes in trophic support (Chen et al, 1997) or in neuronal activity (Grill and Riddle, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant reduction of dendritic spines on the hippocampal neurons would be the underlying cause. It would appear therefore that dendritic change is a common feature affecting most central neurons such as pyramidal neurons in the medial prefrontal cortex (Grill and Riddle, 2002), motor cortices (Nakamura et al, 1985) and hippocampus (Luine et al, 2011), cerebellar Purkinje neurons (Zhang et al, 2010) and retinal ganglion cells (Samuel et al, 2011). It is suggested that regression in dendritic arbor and loss of dendritic spines on layer III, layer V primary somatosensory cortical neurons or hippocampal CA1 pyramidal neurons as observed in this study in aging rats may reflect different degrees of degenerative changes that might be induced by regional changes in trophic support (Chen et al, 1997) or in neuronal activity (Grill and Riddle, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Further, multi-joint movement requires precise control of joint interaction torques (Gribble and Ostry 1999), thought to be centrally mediated by proprioceptive feedback (Sainburg et al 1995, Verschueren et al 1999. Older adults may be unable to sufficiently compensate for interaction torques due to agerelated degeneration of the cerebellum (Zhang et al 2010), an important site for proprioceptive information integration (Jueptner and Willer 1998). Since age-related declines in cognitive function may impair the ability to integrate multiple sources of sensory feedback (Brauer et al 2001;), differences in proprioceptive acuity between young and older adults may persist when performing multijoint matching movements.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has observed that while there is a stable number of Purkinje cells in the cerebellum with aging, there are some sections of the cerebellum, such as the anterior lobe, in which a loss of these cells is observed with aging (Andersen, Gundersen, and Pakkenberg 2003;Zhang, Zhu, and Hua 2010). As our analysis consisted of the entire cerebellum samples, this region-specific effect might be lost.…”
Section: Caspases Expression and Processing Of Stk3 In The Brainmentioning
confidence: 91%